PENTINGNYA MEMBANGUN KEKUATAN BRAND ASSOSIATION SEBAGAI STRATEGI MENINGKATKAN LOYALITAS PELANGGAN - Anshori, Muhammad Amir; Saefudin; Ariyadi, Muhammad Yusuf; Augtiah, Imfrianti; Kurniawati, Hasni Dyah; Anafih, Erwinda Sam (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Companies must be able to retain customers in various ways, including by emphasizing brand image that can attract new customers, and customer happiness that can create customer loyalty. Customer loyalty is one of the most significant variables in maintaining company growth and expanding its sales. Many public figures open companies, including restaurants and snacks. Many entrepreneurs who are involved in the business sector have prominent names to build a positive brand image in the eyes of consumers. This research was conducted at Ayam Geprek Sako with a sample of 160. This study combines descriptive and quantitative methods. This study was conducted to determine the relationship between three variables, namely brand association, Customer Satisfaction, and Customer Loyalty. This study uses primary and secondary sources to obtain its data. The survey method will be used to collect primary data, while secondary data sources such as books, journals, and articles from previous studies will be used to obtain secondary data. Analysis with SEM PLS. the results show that Brand Association Strength has an effect on satisfaction and does not have an effect on loyalty. And satisfaction can mediate between brand association and loyalty.